Oracle inequalities for weighted group lasso in high-dimensional misspecified Cox models - Yijun Xiao; Ting Yan; Huiming Zhang; Yuanyuan Zhang (Journal of Inequalities and Applications, 2020)
Abstract We study the nonasymptotic properties of a general norm penalized estimator, which include Lasso, weighted Lasso, and group Lasso as special cases, for sparse high-dimensional misspecified Cox models with time-dependent covariates. Under suitable conditions on the true regression coefficients and random covariates, we provide oracle inequalities for prediction and estimation error based on the group sparsity of the true coefficient vector. The nonasymptotic oracle inequalities show that the penalized estimator has good sparse approximation of the true model and enables to select a few meaningful structure variables among the set of features.